(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the degree of possession of physical education teachers of methods of resolving conflicts by peaceful means among primary school students, the researcher followed the descriptive analytical approach, and the research sample included (270) teachers, including (126) teacher, and (144) teacher, the research includes a tool represented in the identification of methods of resolving disputes by peaceful means consisting of (30) paragraphs distributed over five areas, namely (dialogue, student mediation, negotiation, waiver, cooperation), and the results showed: The degree of possession of teachers of physical education methods of conflict resolution from their point of view as a whole was average, as the total arithmetic average (3.67), with a standard deviation of (0.76) and the degree of average, either the order of the fields was the third area in the first place and a high degree, and the fifth area in the last place and the degree of average, and in light of the results of the research put forward the researcher several recommendations and proposals.